Inoculation of barley with Trichoderma harzianum T-22 modifies lipids and metabolites to improve salt tolerance. (19th July 2021) - Gupta, Sneha; Smith, Penelope M C; Boughton, Berin A; Rupasinghe, Thusitha W T; Natera, Siria H A; Roessner, Ute
Abstract : The fungus Trichoderma harzianum alleviated the effect of salt stress in a sensitive barley cultivar and improved growth of a tolerant cultivar by changing their root metabolite and lipid profile. Abstract: Soil salinity has a serious impact on plant growth and agricultural yield. Inoculation of crop plants with fungal endophytes is a cost-effective way to improve salt tolerance. We used metabolomics to study how Trichoderma harzianum T-22 alleviates NaCl-induced stress in two barley ( Hordeum vulgare L.) cultivars, Gairdner and Vlamingh, with contrasting salinity tolerance. GC-MS was used to analyse polar metabolites and LC-MS to analyse lipids in roots during the early stages of interaction with Trichoderma . Inoculation reversed the severe effects of salt on root length in sensitive cv. Gairdner and, to a lesser extent, improved root growth in more tolerance cv. Vlamingh. Biochemical changes showed a similar pattern in inoculated roots after salt treatment. Sugars increased in both cultivars, with ribulose, ribose, and rhamnose specifically increased by inoculation. Salt stress caused large changes in lipids in roots but inoculation with fungus greatly reduced the extent of these changes. Many of the metabolic changes in inoculated cv. Gairdner after salt treatment mirror the response of uninoculated cv. Vlamingh, but there are some metabolites that changed in both cultivars only after fungal inoculation. Further study is required to determine how these metabolic changes are induced by fungal inoculation.